ANALISIS PERAN GURU DALAM MEMBENTUK KARAKTER DISIPLIN MELALUI MATA PELAJARAN PENDIDIKAN PANCASILA PADA SISWA SDN KEBON JERUK 06 PAGI - Widia Istikomah; Nurul Febrianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the role of teachers in forming students disciplinary character trough the Pancasila Education subject for students at SDN Kebon Jeruk 06 Pagi, and wants to know the factors inhibiting teachers in the process of forming students disciplinary character. The research method used was descriptive qualitative. The data collection techniques used were observation, interviews and documentation. The research results obtained are the role of the teacher as : (1) The teacher as a role model, by providing good concrete examples to students. (2) The teacher as an inspiration, by exploring students interests and talents and providing ideas and opportunities for students to be able to develop their interests and talents. (3) Teachers as motivators, by providing encouragement to students regarding positive things and the consequences of negative things they do and students knowing the consequences (4) Teachers as facilitators, by providing the equipment students need in the learning process and the continuity of character education at school, and the role model of the teacher is realized through the value of a positive attitude towards Pancasila Education subjects. The challenges and obstacles’ disciplinary character are students’ lack of understanding and lack of consistency regarding school regulations as well as family and environmental factors.